Co-Detection of VEGF-A and Its Regulator, microRNA-181a, May Indicate Central Nervous System Involvement in Pediatric Leukemia - Bálint Egyed; Bálint Egyed; Bálint Egyed; Anna Horváth; Ágnes F. Semsei; Csaba Szalai; Judit Müller; Dániel J. Erdélyi; Gábor T. Kovács (Frontiers Media S.A., 2022)
Central nervous system (CNS) involvement is a leading cause of therapy-refractory pediatric acute lymphoblastic leukemia (pALL), which is aggravated by underdiagnosing CNS disease with the currently used cell-based approach of cerebrospinal fluid (CSF) diagnostics. Our study focused on developing novel subcellular CNS leukemia indicators in the CSF and the bone marrow (BM) of patients with pALL. Serial liquid biopsy samples (n = 65) were analyzed by Elisas to measure the level of essential proteins associated with blast cell CNS trafficking, vascular endothelial growth factor A (VEGF-A) and integrin alpha 6 (ITGA6). In CSF samples from early induction chemotherapy, VEGF-A concentration were uniformly elevated in the CNS-positive group compared to those patients without unambiguous meningeal infiltration (9 vs Nine patients, Δc = 17.2 pg/ml, p = 0.016). Expression of miR-181a, a VEGFA-regulating microRNA which showed increased level in CNS leukemia in our previous experiments, was then paralleled with VEGF-A concentration. A slight correlation between the levels of miR-181a and VEGF-A indicators in CSF and BM samples was revealed (n = 46, Pearson's r = 0.36, p = 0.015). After validating in international cohorts, the joint quantification of miR-181a and VEGF-A might provide a novel tool to precisely diagnose CNS involvement and adjust CNS-directed therapy in pALL.